African American Cultural Identity Reflected in Hurston’s Every Tongue Got To Confess - Kusumajanti, Wahju; Ramadhani, Alifia (Proceedings of International Conference on Islamic Civilization and Humanities, 2023)
Zora Neale Hurston was one of the outstanding African American writers. Her last work resulted from her anthropological study of African American folklore in the South. This study explores African American cultural identity through traditions and storytelling practices within the African American community in the United States in Hurston’s Every Tongue Got To Confess. Using Hall’s theory of cultural identity, this research investigates how these traditions were influenced by African diasporic roots, as well as the unique experiences of African Americans in the United States. It is found that African American shaped their identity through spiritual and religious practices.